Memes in theater: tensions in the transposition of internet comic discourse to the stage - Barzague Lobato Pereira, Brian; Castro de Souza, Raquel (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This article explores the process of transposing the internet meme to the theater based on the analysis of three theatrical works: Roda Viva (2018), by Teatro Oficina; Sísifo (2019), by Gregório Duvivier and Vinícius Calderoni; and the short scene La fama (2023), presented by the authors of the article - together with the actors of Cia de Sucesso. The aim is to understand what the appropriation of these digital items and their different mimetic approaches on stage generates in the understanding of theater itself as a way of circulating social mentalities. The humorous character of the meme is highlighted to suggest, based on studies on laughter and comedy - particularly the works of Michael Billig (2005) and Bergson (2004) - that there is a qualitative change in the attributes of the comic that explain the humorous nature of memes (Shifman, 2014, p. 79). It is concluded that the theatrical mimicry of the meme does not imply that the scene becomes a meme, and that, although it contributes to the replication of the reference to which it relates, it proposes unprecedented modifications of posture (stance). The article is one of the results of the research “Archive of the Intercultural Memory of the Performing Arts in Brazil”, financed by FAPEMIG.